Terapeutic eficacity testing of Rombendazol 10% (Romvac) and Fasinex (Novartis) in natural infestation with Fasciola hepatica at sheep from Bilbor, Harghita County - Tifrea, M.,; Oprescu, I.,; Indre, D.,; Mirela Imre,; Darabus, Gh. (Medicamentul Veterinar)
The study was carried out between January -February 2008, on 30 sheep Tigaie and Turcana breeds from Bilbor, Harghita County. Animals were distributed randomly into three groups (n = 10): group A1 (treated with albendazole), group B1 (treated with triclabendazole) and control group (M) - the dosage used was the one recommended by the producer. Coproscopical examination was made on days 0 and 14 using the methods recommended by WAAVP and the efficacy was evaluated using Presidente relation. Investigations revealed an efficacy value of 98.35% for Fasinex and 71.55% for Rombendazol 10%.